AI Cities Strategy Conceptual Model: Application to Four Cities: New York, Buenos Aires, Barcelona and Madrid - Fernández Añez, María Victoria (Street Art & Urban Creativity, 2025)
This paper develops and applies a systemic conceptual model to analyze how cities integrate artificial intelligence (AI) into urban governance through AI strategies. The conceptual model interrelates three core components—stakeholders, urban systems (spatial, technological, and service-based), and strategic objectives—to interpret AI strategies in New York, Buenos Aires, Madrid, and Barcelona. The model enables comparative analysis and supports the design of adaptable, inclusive, and sustainable AI strategies. By synthesizing diverse urban experiences, the study proposes a flexible framework for guiding future AI-driven urban transformation initiatives in an integrated way, opening paths to understand relations other aspects of the city.